A systematic review of microsurgical reconstruction of the jaws using vascularized fibula flap technique in patients with bisphosphonate-related osteonecrosis - Roberto Sacco; Gianluca Sacco; Alessandro Acocella; Silvana Sale; Nicola Sacco; Edoardo Baldoni (University of São Paulo, 2011)
OBJECTIVE: The aim of this systematic review was to assess the role of microsurgical reconstruction of the jaws in patients with bisphosphonate-related osteonecrosis, and biological complications after an observation period of at least 12 months. Material and methods: An electronic MEDLINE search supplemented by manual searching was conducted to identify studies reporting data of at least 12 months observation on the microsurgical reconstruction of the jaws in patients with bisphosphonate-related osteonecrosis. RESULTS: Four studies resulted eligible for the analysis yielded. Three out of five studies were free of complications, with a success rate of 100% as no recurrence of osteonecrosis was registered. CONCLUSIONS: Microsurgical reconstruction of the jaws represents a valid treatment modality in patients with bisphosphonate-related osteonecrosis at 3rd stage of the disease.